2017
DOI: 10.1352/1944-7558-122.6.476
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Phonological Awareness Skills in Children With Intellectual Disability

Abstract: The phonological awareness skills of 7- to 8-year-old children with intellectual disability (ID) were compared to those of 4- to 5-year-old typically developing children who were matched for early reading skills, vocabulary, and gender. Globally, children with ID displayed a marked weakness in phonological awareness. Syllable blending, syllable segmentation, and first phoneme detection appeared to be preserved. In contrast, children with ID showed a marked weakness in rhyme detection and a slight weakness in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 57 publications
1
14
0
8
Order By: Relevance
“…In ADHD, the lack of attention prevents important information for development of metalinguistic abilities to be retained 6 . Lastly, in intellectual disability, phonological awareness is an ability significantly affected, especially in rhyme detection and phonemic manipulation, due to failures in short-term phonological memory 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ADHD, the lack of attention prevents important information for development of metalinguistic abilities to be retained 6 . Lastly, in intellectual disability, phonological awareness is an ability significantly affected, especially in rhyme detection and phonemic manipulation, due to failures in short-term phonological memory 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Differences were observed in the phonological working memory and the phonological awareness tests between the three groups. Hence, it is noted that the phonological processing may differ in the neurodevelopmental disorders with distinct etiologies 7,11,19,20 . This may be due to the different cognitive profiles of the conditions, reinforcing that they refer to different disorders 5,6,11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…PA and letter-sound knowledge were found to be significant predictors of word identification and reading comprehension in different profiles of children with ID ( Kennedy and Flynn, 2002 ; Laing et al., 2001 ; Laws and Gunn, 2002 ; Levy et al., 2003 ; Menghini et al., 2004 ; Sermier Dessemontet and de Chambrier, 2015 ; Snowling et al., 2002 ). On the other hand, several studies indicate that PA is an area of weakness in children with ID of different etiologies ( Adlof et al., 2015 ; Laing et al., 2001 ; Lemons and Fuchs, 2010 ; Menghini et al., 2004 ; Sermier Dessemontet et al., 2017 ). PA of children with ID is also marked by an atypical pattern of development.…”
Section: Theorymentioning
confidence: 99%
“…PA of children with ID is also marked by an atypical pattern of development. Indeed, it has repeatedly been found that these children especially struggle in rhyme awareness while achieving some phonemic tasks better (e.g., first phoneme detection) in contrast to their TD peers ( Sermier Dessemontet et al., 2017 ; Snowling et al., 2002 ; Steele et al., 2013 ).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation